The Italian startup act: A microeconometric program evaluation - Francesco Biancalani; Dirk Czarnitzki; Massimo Riccaboni (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper analyses the impact of the Italian Startup Act which entered into force in December 2012. This public policy provides a unique bundle of benefits, such as tax incentives, public loan guarantees, and a more flexible labor law, for firms registered as "innovative startups" in Italy. This legislation has been implemented by the Italian government to increase innovativeness of small and young enterprises by facilitating improved access to (external) capital and (highskilled) labor. Consequently, the goal of our evaluation is to assess the impact of the policy on equity, debt and employment. Using various conditional difference-in-difference models, we find that the Italian startup policy has met its primary objectives. The econometric results strongly suggest that firms operating under this program are more successful in obtaining equity and debt capital and they also hire more employees because of the program participation.
Keywords: M13; O38; 330; start up; innovation policy; firm subsidies; small firms